METODE PELAKSANAAN PENGUJIAN PONDASI TIANG PANCANG MENGGUNAKAN (PDA TEST) PADA PROYEK PEMBANGUNAN GEDUNG PORTIR DAN AULA LAPAS KELAS I MEDAN - Sihotang, Harlen; Panjaitan, Alfin (Jurnal Sains dan Teknologi ISTP, 2024)
In proving the strength of the finished pile foundation, further testing must be carried out. The Medan Class I Porter Building and Penitentiary Hall Construction Project was carried out by the PDA test (Pile Driving Analyzer) which is a dynamic test used to measure the bearing capacity of piles, ultimate axial compressive resistance of piles, and so on. The aim of this research is to ascertain and ascertain whether the method for carrying out PDA testing carried out in the Medan Class I Prison Building and Prison Hall Construction Project is appropriate or not by referring to SNI 8459:2017 and the guidebook issued by the Regulations regarding base tests in building structure SNI 03-2847-2013[4]. The method used in this research is a qualitative method, where the data in this research is obtained from direct observation and interviews in the field as primary data and from data testing and data specifications of various secondary data. These two regulations will compare in the field according to the standard which refers to foundation tests on building structures, namely SNI 03-2847-2013 and also refers to SNI 8459:2017 concerning the method of testing deep foundations with High-Strain Dynamic Pile (HSDP) which is where the PDA test is included in the HSDP test. This discussion will focus on testing after the foundation has been worked on in the field.